GEOIDAL UNDULATION AND GRAVITY ANOMALY AROUND ANTARCTICA FROM GEOSAT SATELLITE ALTIMETRY - フクダ, ヨウイチ; セガワ, ジロウ; FUKUDA, Yoichi; SEGAWA, Jiro (National Institute of Polar Research, 1989)
P(論文) GEOSAT altimeter data were processed to obtain an altimetric geoid and gravity anomalies around Antarctica. As GEOSAT is the first satellite which can reveal the sea surface heights of the Antarctic summer seasons, it is strongly expected to provide new knowledge concerning the gravity fields in the Antarctic Ocean. The data employed in this study were obtained during one repeat cycle of the GEOSAT Exact Repeat Mission (ERM). Geophysical corrections and crossover adjustments were made to obtain an altimetric geoid, and altimetric gravity anomalies were calculated by means of the FFT method. The results were compared with those of the former studies and the improvement of the accuracy near the Antarctic Continent was confirmed. departmental bulletin paper